Purification and Partial Characterization of Lectins from In vitro Cultures of Ricinus communis - Chaudhary, Harshita; Sood, Neelu (Plant Tissue Culture and Biotechnology, 2009)
Ricinus lectins have proven to be quite useful in biological and medical research because of their haemagglutinating, mitogenic, antitumor and toxic properties. In the Indian medicine system, the leaf, root and seed oil of this plant species have been used for the treatment of inflammation and liver disorders. The two major lectins Ricin and RCA have toxic and haemagglutination activities. The micropopagation of Ricinus was standardized using MS medium supplemented with different concentrations of IAA, IBA, NAA, BAP and Kinetin. Kinetin (0.5 mg/l) + NAA (1.0 mg/l) combination was found to be optimal for raising in vitro complete plants within 4 weeks. Using Affinity chromatography galactose binding lectins were isolated from the in vitro grown plants, in vivo leaves and mature seeds. The isolated fractions were further characterized for their molecular weight using SDS-PAGE, haemagglutination activity, pH and thermostability. In the purified fractions, the protein bands other than those corresponding to reported subunits of Ricinus lectins, indicated the presence of some more hitherto unexplored lectins. However, the seeds proved to be a rich source of lectins more than in in vitro grown plants. The seeds are available only from the mature plant at the end of growing season, hence consistent supply of lectins is not possible using conventional methods. Thus in vitro raised plants can prove to be rich source of lectins other than seeds, which can be of great therapeutic and commercial use. Key words: Ricinus communis, Lectins, In vitro, Micropropagation, Ricin, RCA, Haemagglutination, Purification and Characterization D.O.I. 10.3329/ptcb.v18i2.3269 Plant Tissue Cult. & Biotech. 18(2): 89-102, 2008 (December)